2020
DOI: 10.1101/2020.01.01.20016295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, Characteristics, and Associated Factors of Workplace Violence Against Healthcare Professionals in India: A Systematic Review and Meta-analysis

Abstract: Background: Workplace violence (WPV) against doctors, nurses, and other healthcare professionals is a growing public health concern affecting health systems in low- and middle-income countries. In India, incidents of WPV against health workforce have become common in recent years. However, there is no synthesized evidence on the nationwide burden of WPV in healthcare. This study aims to systematically evaluate the current evidence on the prevalence, characteristics, and associated factors of WPV against health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 70 publications
(196 reference statements)
5
13
0
Order By: Relevance
“…In the journal's earlier issue, the editorial “Death of a doctor - Ek Doctor Ki Maut—Time to boost the ailing and failing public health system in India“,[ 1 ] rightfully presses upon the need to strengthen India's ailing primary healthcare system to prevent workplace violence (WPV) against doctors in India. The severity mentioned in this editorial coincides with the findings of a recent meta-analysis,[ 2 ] which found that the pooled prevalence of WPV among 2849 healthcare providers in India was 63% (95% confidence interval [CI], 54–72%). Moreover, the prevalence of verbal violence (52%; 95% CI, 45–60%) was higher than physical violence (8%; 95% CI, 5–11%),[ 2 ] which highlights the death of a doctor or similar news reporting physical injuries are the tip of the iceberg, where the actual magnitude of WPV is much higher in reality.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…In the journal's earlier issue, the editorial “Death of a doctor - Ek Doctor Ki Maut—Time to boost the ailing and failing public health system in India“,[ 1 ] rightfully presses upon the need to strengthen India's ailing primary healthcare system to prevent workplace violence (WPV) against doctors in India. The severity mentioned in this editorial coincides with the findings of a recent meta-analysis,[ 2 ] which found that the pooled prevalence of WPV among 2849 healthcare providers in India was 63% (95% confidence interval [CI], 54–72%). Moreover, the prevalence of verbal violence (52%; 95% CI, 45–60%) was higher than physical violence (8%; 95% CI, 5–11%),[ 2 ] which highlights the death of a doctor or similar news reporting physical injuries are the tip of the iceberg, where the actual magnitude of WPV is much higher in reality.…”
supporting
confidence: 88%
“…The severity mentioned in this editorial coincides with the findings of a recent meta-analysis,[ 2 ] which found that the pooled prevalence of WPV among 2849 healthcare providers in India was 63% (95% confidence interval [CI], 54–72%). Moreover, the prevalence of verbal violence (52%; 95% CI, 45–60%) was higher than physical violence (8%; 95% CI, 5–11%),[ 2 ] which highlights the death of a doctor or similar news reporting physical injuries are the tip of the iceberg, where the actual magnitude of WPV is much higher in reality. A robust primary care system can decongest the over-burdened tertiary care hospitals, preventing their overcrowding—a major precipitating factor for WPV against doctors and other healthcare professionals.…”
supporting
confidence: 88%
See 3 more Smart Citations